Improving Students Speaking Ability By Using Talking Stick Method In The Eight Grade Of SMP Swasta GKPS 3 Pematangsiantar - Marhaeni K D Matondang; Nurinda Nababan (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
The aim of this research was to find out improving speaking ability by using talking stick method of the eight grade students at SMP SWASTA GKPS 3 PEMATANGSIANTAR. This research were done to know and identified about the improvement of student’s speaking ability by using talking stick and students’ response toward using talking stick. This research was conducted on July until August 2021. This research classified as one class. It involved 30 students. The design of this research is used pre-experimental with quantitative approach. In collecting the data the researcher use pre-test and post- test. The result shows that by using talking stick method has improved the students’ motivation, score and response were good. The improvement of students achievement are proved from pre-test and post-test result. The mean score in pre-test is 44% and the mean score in post-test is 84% and the standard deviation is 45.63%. So, from the mean score and the standard deviation result shows that the students’ speaking ability is improved become excellent level after using talking stick method at the eight grade of SMP SWASTA GKPS 3